A detailed observation of the ejection and retraction of defense tissue acontia in sea anemone (Exaiptasia pallida) - Lam, Julie (PeerJ, 2017)
Acontia, located in the gastrovascular cavity of anemone, are thread-like tissue containing numerous stinging cells which serve as a unique defense tissue against predators of the immobile acontiarian sea anemone. Although its morphology and biological functions, such as defense and digestion, have been studied, the defense behavior and the specific events of acontia ejection and retraction are unclear. The aim of this study is to observe and record the detailed process of acontia control in anemones. Observations reveal that the anemone, Exaiptasia pallida, possibly controls a network of body muscles and manipulates water pressure in the gastrovascular cavity to eject and retract acontia. Instead of resynthesizing acontia after each ejection, the retraction and reuse of acontia enables the anemone to respond quickly at any given time, thus increasing its overall survivability. Since the Exaiptasia anemone is an emerging model for coral biology, this study provides a foundation to further investigate the biophysics, neuroscience, and defense biology of this marine model organism.